Effect of Solid and Liquid Extracts of Lombok Sargassum cristafolium on Growth and Yield of Rice Plants (Oryza sativa L.) - Haji Sunarpi; Aluh Nikmatullah; Anggit L. Sunarwidhi; Yogi Ambana; Bq Tri Khairina Ilhami; Sri Widyastuti; Ari Hernawan; Eka Sunarwidhi Prasedya (Jurnal Biologi Tropis, 2020)
An exessive use of inorganic fertilizers in agriculture cultivation system causes many disadventages, such as increase cost production, reduce farmerÃ¢â¬â¢s income and soil fertility, and harm our environment. Therefore, it is needed to find out raw materials for development of organic biostimulant and biofertilizer inducing essential element absorption, growth and yield of plants, which are adaptive to our environment as well. Previous researchres reported that seaweed contained plant growth hormones and essential elements in liquid and solid extracts respectively. This article reports effect of solid and liquid extracts of Sargassum cristafolium on growth and yield of rice plants. The extracts were extracted according to modified procedure.. Solid extract (350 gr) of Sargassum cristafolium was mixed with soil (6650 gr) to become 7 kg soil media. Moreover, liquid extract (10%) of Sargassum cristafolium was sprayed to rice plants once a week during vegetative growth. The results shown that addition of 350 gr of solid extract to soil media increased growth (plant high, tiller number, shoot dry weight and root dry weight) and yield (penicle number and grain weight per plants) significantly compared with those of plants which were not supplied with solid extract. However, spraying liquid extract of Sargassum cristafolium did not affet significantly growth and yield of rice plants, even small change happen in growth and yield parameters of the rice plants supplied with solid extract. This indicates that solid extract is a potential source for development of biofertilizer which is adaptive to our environment to support sustainable agriculture system.